BAROTRAUMA SEBAGAI FAKTOR RISIKO PENDUDUK PESISIR PANTAI - Raisa Astasia; I Gusti Ayu Trisna Aryani (Jurnal Medika Hutama, 2023)
Barotrauma is tissue damage due to changes in barometric pressure that occurs when diving or flying. Barotrauma can occur when the gas-filled spaces in the body become closed spaces by blocking the normal ventilation pathways. The pathophysiology of this disease is based on Boyle's law which states that a decrease or increase in environmental pressure will increase or suppress (respectively) a volume of gas in a confined space. If the gas is present in a flexible structure, the structure can be damaged by expansion or compression. Symptoms of this disease can be divided into 2, namely symptoms of descent and ascent. Barotrauma can be managed quite simply by administering decongestants and avoiding diving or flying until the patient is able to balance middle ear pressure again.